Media Practitioners' Perspective On News Media Reporting Of Islam And Muslims: A Room For Improvement Through A Formulation Of Writing News Guideline - Fauziah Hassan; Sofia Hayati Yusoff; Osama Kanaker; Muhamad Zaki Mustafa (Universiti Sains Islam Malaysia, 2024)
Vol. 23 No. 2 (2020): Journal of Islamic Social Sciences and Humanities (Special Issue)